The water gas shift reaction over Pt–CeO2 nanoparticles confined within mesoporous SBA-16. Issue 37 (14th September 2017) - Carta, D.; Montini, T.; Casula, M. F.; Monai, M.; Bullita, S.; Fornasiero, P.; Corrias, A.
Abstract : Pt–CeO2 nanoparticles confined in mesoporous silica SBA-16 as successful catalysts for the single step, low temperature water gas shift reaction. Abstract : Novel nanocomposite catalysts for the single step Water Gas Shift Reaction (WGSR) were prepared by deposition–precipitation and impregnation of Pt–CeO2 nanophases onto an ordered mesoporous silica support featuring a cubic arrangement of mesopores (SBA-16 type). The highly interconnected porosity of the SBA-16 developed in three dimensions (3D) provides a scaffold which is easily accessible to reactants and products by diffusion. The textural and morphological properties of the final catalyst were affected by the procedure utilized for dispersion of the nanophases onto SBA-16. The catalysts prepared by deposition–precipitation present highly dispersed nanocrystalline CeO2 on the surface of SBA-16 and retain a high surface area, high thermal stability and high Pt accessibility. The catalysts prepared by impregnation show improved Pt–CeO2 interaction but a more significant decrease of surface area compared to pure SBA-16, due to the confinement of the CeO2 crystallites within the mesoporous matrix. As a result, the catalysts prepared by deposition–precipitation are effective for the WGSR under working conditions in the high temperature range (around 300–350 °C), whereas the catalysts prepared by impregnation are suitable for the process operating at low temperature. Our results point out that these catalyst preparation procedures can be used to optimise the performance of heterogenous catalysts, by controlling the CeO2 crystallite size and optimizing the Pt–CeO2 contact by embedding. Improved thermal and chemical stabilities were achieved using a mesoporous scaffold.